Combined genotype and haplotype distributions of MTHFR C677T and A1298C polymorphisms: A cross-sectional descriptive study of 13, 473 Chinese adult women. Issue 48 (November 2016) - Fan, Shujun; Yang, Boyi; Zhi, Xueyuan; Wang, Yanxun; Zheng, Quanmei; Sun, Guifan
Abstract : Abstract: Methylenetetrahydrofolate reductase ( MTHFR ) C677T and A1298C polymorphisms are, independently and/or in combination, associated with many disorders. However, data on the combined genotype and haplotype distributions of the 2 polymorphisms in Chinese population were limited. We recruited 13, 473 adult women from 9 Chinese provinces, collected buccal cell samples, and determined genotypes, to estimate the combined genotype and haplotype distributions of the MTHFR C677T and A1298C polymorphisms. In the total sample, the 6 common combined genotypes were CT/AA (29.5%), TT/AA (21.9%), CC/AA (15.4%), CC/AC (14.9%), CT/AC (13.7%), and CC/CC (3.4%); the 3 frequent haplotypes were 677T-1298A (43.6%), 677C-1298A (37.9%), and 677C-1298C (17.6%). Importantly, we observed that there were 51 (0.4%) individuals with the CT/CC genotype, 92 (0.7%) with the TT/AC genotype, 17 (0.1%) with the TT/CC genotype, and that the frequency of the 677T-1298C haplotype was 0.9%. In addition, the prevalence of some combined genotypes and haplotypes varied among populations residing in different areas and even showed apparent geographical gradients. Further linkage disequilibrium analysis showed that the D' and r 2 values were 0.883 and 0.143, respectively. In summary, the findings of our study provide further strong evidence that the MTHFR C677T and A1298C polymorphisms are usually in trans and occasionally in cis configurations. The frequencies of mutant genotype combinations were relatively higher in Chinese population than other populations, and showed geographical variations. These baseline data would be useful for future related studies and for developing health management programs.